IMPLEMENTASI KEBIJAKAN KARTU PERLINDUNGAN SOSIAL DI DESA GUMPA KECAMATAN DUSUN TIMUR KABUPATEN BARITO TIMUR ( STUDI PROGRAM BANTUAN SISWA MISKIN ) - Nurmalasyiah, Nurmalasyiah (stiatabalong.ac.id, 2017)
By Minister of Internal Affairs Instruction 542/3150 / SJ on Implementation pembangian Social Security Card and Handling Public Complaints that the Social Protection Card (KPS) is a card issued by the Government as a marker of poor households. PPP contains information other household members, household address, family card numbers, equipped with a bar code (barcode) and KPS unique identity number. The front of the card reads Social Protection with Garuda logo and card expiration. The purpose of writing this study is to identify and analyze Implementation of Social Protection Card Program In the village hamlet Gumpa Eastern District of East Barito District (Study Help Poor Students).The research method using descriptive qualitative approach, data collection was done by interview using the theory Grindle, respondents used is of poor students who receive assistance, data analysis techniques using the theory Milles, Huberman and Saldana, 2014Protection Card Gumpa In the village of Dusun Eastern District of East Barito District (Study Help Poor Students) already performing well. However, there are some that are a barrier that is the less accurate data collection on poor students, the use of funds BSM is not maximized, because it is used for other purposes.So the hope is that this program viable or sustainable, with the correct data collection in accordance with the facts on the ground.  Keywords: Implementation, Program Policy KPS